2023
DOI: 10.1101/2023.09.24.559195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SDC4 deletion perturbs intervertebral disc matrix homeostasis and promotes early osteopenia in the aging spine

Kimheak Sao,
Makarand V. Risbud

Abstract: Syndecan 4 (SDC4), a cell surface heparan sulfate proteoglycan, is known to regulate matrix catabolism by nucleus pulposus cells in an inflammatory milieu. However, the role of SDC4 in the aging spine has never been explored. Here we analyzed the spinal phenotype of SDC4 global knockout (KO) mice as a function of age. Micro computed tomography showed that SDC4 deletion severely reduced vertebral trabecular and cortical bone mass, and biomechanical properties of vertebrae were significantly altered in SDC4 KO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Importantly, the transcriptomic analysis suggested that Sdc4 deletion downregulates genes associated with mitochondrial metabolism, autophagy, ER to Golgi protein processing, and HS biosynthesis and GAG degradation. These findings indicate that deletion of Sdc4 reduces matrix turnover which is speculated to be responsible for CS accumulation and GAG degradation in NP tissue [ 107 ]. Other investigators using Has2 - and Sulf1 -knockout mice have demonstrated the important of GAG function in PGs.…”
Section: Proteoglycan-linked Disc Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the transcriptomic analysis suggested that Sdc4 deletion downregulates genes associated with mitochondrial metabolism, autophagy, ER to Golgi protein processing, and HS biosynthesis and GAG degradation. These findings indicate that deletion of Sdc4 reduces matrix turnover which is speculated to be responsible for CS accumulation and GAG degradation in NP tissue [ 107 ]. Other investigators using Has2 - and Sulf1 -knockout mice have demonstrated the important of GAG function in PGs.…”
Section: Proteoglycan-linked Disc Pathologiesmentioning
confidence: 99%
“…These findings indicate that deletion of Sdc4 reduces matrix turnover which is speculated to be responsible for CS accumulation and GAG degradation in NP tissue. 107 Other investigators using Has2-and Sulf1-knockout mice have demonstrated the important of GAG function in PGs. Changes in hyaluronan synthesis and sulfation of GAG profiles can alter the structure and function of PGs.…”
Section: Proteoglycan-linked Disc Pathologiesmentioning
confidence: 99%